The Nature of Countercyclical Income Risk - Guvenen, Fatih; Ozkan, Serdar; Song, Jae (Journal of Political Economy, 2014)
We study business cycle variation in individual earnings risk using a confidential and very large data set from the US Social Security Administration. Contrary to past research, we find that the variance of idiosyncratic shocks is not countercyclical. Instead, it is the left-skewness of shocks that is strongly countercyclical: during recessions, large upward earnings movements become less likely, whereas large drops in earnings become more likely. Second, we find that the fortunes during recessions are predictable by observable characteristics before the recession. Finally, the cyclicality of earnings risk is dramatically different for the top 1 percent compared with the rest of the population.